I wonder why snakes shed their skins and other questions about reptiles - O'Neill, Amanda (London Kingfisher, 2007)
Answers such questions about reptiles as why do snakes stare, are frogs and newts reptiles, and which reptile lives longest.
Includes index.
Keywords: Reptiles -- Miscellanea -- Juvenile literature; Reptiles -- Miscellanea; Questions and answers